Research On the Study of The Specific Activity of a Medicinal Substance with Gold Nanoparticles - Kamal Saidakbarovich, Rizaev; Iroda Bakhtiyor Qizi, Shermatova (Journal of Neonatal Surgery, 2025)
The paper presents the results of a study on the specific activity of the medicinal substance "Dry extract of Scutellaria Iscandera L. herb with gold nanoparticles". The ability of gold nanoparticles to act both as a component generating active forms of oxygen and to inhibit the oxidation process by absorbing free radicals can be used to create new drugs that combine antioxidant potential and antibacterial efficacy. The results of the studies showed that the diameter of growth inhibition of Staphylococcus epidermidis and Pseudomonas aeuruginosa was 33-38 mm and 30-34 mm, respectively. The antimicrobial activity of the studied samples showed a high rating against Escherichia coli - where the diameter of the inhibition zone was 24-28 mm, Bacillus subtillis - 20-25 mm, Bacillus pumilus 21-25 mm and Candida albicans was 32-37 mm, Staphylococcus aureus 20-25 mm.